There for the Reaping: The Ethics of Harvesting Online Data for Research Purposes - Zia, Sadaf; De Lancey, Celina; Regan, Priscilla; Burkell, Jacquelyn (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2020)
Online social environments offer a rich source of data that researchers can harvest to gain insight into a wide range of social issues. This type of research is sometimes considered as observation of public behaviour, and therefore exempt from ethical review. This type of research, however, raises ethical issues with respect to the public/private nature of online spaces, consent, and anonymity in the online environment. This project examines research ethics guidelines for recommendations regarding the use of harvested online data, identifying best practices for researchers who engage in this type of research. Les media sociaux offrent une riche source de données que les chercheurs peuvent récolter pour mieux comprendre un large éventail de problèmes sociaux. Ce type de recherche est parfois considéré comme une observation du comportement du public, et donc exempt de tout examen éthique. Ce type de recherche, cependant, soulève des problèmes éthiques en ce qui concerne la nature publique / privée des espaces en ligne, le consentement et l'anonymat dans l'environnement en ligne. Ce projet examine les lignes directrices en matière d'éthique de la recherche pour des recommandations concernant l'utilisation des données récoltées en ligne, identifiant les meilleures pratiques pour les chercheurs qui s'engagent dans ce type de recherche.